Ultra-fast triplet-triplet-annihilation-mediated high-lying reverse intersystem crossing triggered by participation of nπ-featured excited states - Luo, Yanju; Zhang, Kai; Ding, Zhenming; Chen, Ping; Peng, Xiaomei; Zhao, Yihuan; Chen, Kuan; Li, Chuan; Zheng, Xujun; Huang, Yan; Pu, Xuemei; Liu, Yu; et al. (Nature communications, 2022)
The harvesting of ‘hot’ triplet excitons through high-lying reverse intersystem crossing mechanism has emerged as a hot research issue in the field of organic light-emitting diodes. However, if high-lying reverse intersystem crossing materials lack the capability to convert ‘cold’ T 1 excitons into singlet ones, the actual maximum exciton utilization efficiency would generally deviate from 100%. Herein, through comparative studies on two naphthalimide-based compounds CzNI and TPANI, we revealed that the ‘cold’ T 1 excitons in high-lying reverse intersystem crossing materials can be utilized effectively through the triplet-triplet annihilation- mediated high-lying reverse intersystem crossing process if they possess certain triplet-triplet upconversion capability. Especially, quite effective triplet-triplet annihilation- mediated high-lying reverse intersystem crossing can be triggered by endowing the high-lying reverse intersystem crossing process with a 3 ππ*→ 1 nπ* character. By taking advantage of the permanent orthogonal orbital transition effect of 3 ππ*→ 1 nπ*, spin–orbit coupling matrix elements of ca. 10 cm −1 can be acquired, and hence ultra-fast mediated high-lying reverse intersystem crossing process with rate constant over 10 9 s −1 can be realized. Here, the authors investigate naphthalimide-based compounds with cold triplet excitons utilized by triplet-triplet annihilation-mediated high-lying reverse intersystem crossing, and realize rate constant of over 10 9 s −1 with exciton utilization efficiency of 46.7% in organic light-emitting diodes.